THE EFFECT OF PERCEIVED QUALITY, BRAND AWARENESS, AND BRAND LOYALTY TOWARD BRAND EQUITY OF BEER BINTANG IN SURABAYA - Shelly Amelia (Perpustakaan Universitas Surabaya, 2018)
This study aims to observe the effects of Brand Awareness, Perceived Quality, and Brand Loyalty towards Brand Equity of Beer Bintang in Surabaya. Beer Bintang is used as an object in this study. A quantitative and causal type research is adopted for this study. Questionnaire used was adopted from Ha and Jang (2012) for offline survey. Purposive sampling method was used in this study. Sample consisted of 170 respondents, whose age is 18 years old or above and have consume Beer Bintang minimum twice in the past 6 montho in Surabaya. Further data analysis was analyzed by SPSS 18.0 and SEM. Result of this study found positive relationship between perceived quality to brand loyalty. Perceived quality also positively influences brand equity. Positive relationship was also found on the relationship of brand awareness on brand loyalty. Moreover, brand awareness also positively influences brand equity. Additionally, brand loyalty was also has positiv influences to brand equity.